2011
DOI: 10.1016/j.jpsychores.2010.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Intervening on cognitions and behavior in irritable bowel syndrome: A feasibility trial using PDAs

Abstract: A cognitive-behavioral intervention on pocket-type computers appears feasible and efficacious for improving IBS-related complaints and cognitions in the short-term. The intervention group improved on several aspects, but most on catastrophizing thoughts, and these improvements even persisted after 3 months. Future studies should focus on unravelling the effective components of this innovative e-health intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 50 publications
3
70
0
1
Order By: Relevance
“…Table 1 summarises the characteristics of the 24 studies included. Eight chronic health conditions were represented: chronic pain (n = 9 studies) (Andersson, Lundstrom, & Strom, 2003;Brattberg, 2008;Buhrman, Faltenhag, Strom, & Andersson, 2004;Chiauzzi et al, 2010;Devineni & Blanchard, 2005;Lorig, Ritter, Laurent, & Plant, 2008;Ruehlman et al, 2012;Strom, Pettersson, & Andersson, 2000;Williams et al, 2010), diabetes (n = 5) (Glasgow, Boles, McKay, Feil, & Barrera, 2003;Glasgow et al, 2006;Lorig et al, 2010;McKay, Glasgow, Feil, Boles, & Barrera, 2002;McKay, King, Eakin, Seeley, & Glasgow, 2001), irritable bowel syndrome (n = 4) (Hunt, Moshier, & Milonova, 2009;Ljótsson et al, 2010Ljótsson et al, , 2011Oerlemans, van Cranenburgh, Herremans, Spreeuwenberg, & van Dulmen, 2011), tinnitus (n = 2) (Andersson, Stromgren, Strom, & Lyttkens, 2002;Kaldo et al, 2008), fatigue (n = 1) (Ghahari et al, 2010), epilepsy (n = 1) (DiIorio, Bamps, Walker, & Escoffery, 2011), breast cancer (n = 1) (Owen et al, 2005) and other chronic illnesses (n = 1) (Lorig, Ritter, Laurent, & Plant, 2006). Studies were predominantly conducted in the USA (n = 14), with Sweden being second most represented (n = 8; seven of these were conducted by Andersson and colleagues).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarises the characteristics of the 24 studies included. Eight chronic health conditions were represented: chronic pain (n = 9 studies) (Andersson, Lundstrom, & Strom, 2003;Brattberg, 2008;Buhrman, Faltenhag, Strom, & Andersson, 2004;Chiauzzi et al, 2010;Devineni & Blanchard, 2005;Lorig, Ritter, Laurent, & Plant, 2008;Ruehlman et al, 2012;Strom, Pettersson, & Andersson, 2000;Williams et al, 2010), diabetes (n = 5) (Glasgow, Boles, McKay, Feil, & Barrera, 2003;Glasgow et al, 2006;Lorig et al, 2010;McKay, Glasgow, Feil, Boles, & Barrera, 2002;McKay, King, Eakin, Seeley, & Glasgow, 2001), irritable bowel syndrome (n = 4) (Hunt, Moshier, & Milonova, 2009;Ljótsson et al, 2010Ljótsson et al, , 2011Oerlemans, van Cranenburgh, Herremans, Spreeuwenberg, & van Dulmen, 2011), tinnitus (n = 2) (Andersson, Stromgren, Strom, & Lyttkens, 2002;Kaldo et al, 2008), fatigue (n = 1) (Ghahari et al, 2010), epilepsy (n = 1) (DiIorio, Bamps, Walker, & Escoffery, 2011), breast cancer (n = 1) (Owen et al, 2005) and other chronic illnesses (n = 1) (Lorig, Ritter, Laurent, & Plant, 2006). Studies were predominantly conducted in the USA (n = 14), with Sweden being second most represented (n = 8; seven of these were conducted by Andersson and colleagues).…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that some patients do not understand the cognitive behavior model as applying to them and are thus unlikely to engage in CBT [61] . As this is a therapy which makes significant demands on patients' time, some Lynch et al [52] Canada 21 CBT Heymann-Monnikes et al [53] Germany 20 CBT Sanders et al [54] United States 28 CBT Hunt et al [55] United States 54 CBT Moss-Morris et al [56] England 64 CBT Craske et al [40] United States 110 CBT Ljotsson et al [57] Sweden 195 CBT Ljotsson et al [58] Sweden 61 CBT Oerlemans et al [59] The Netherlands 75 CBT CBT: Cognitive-behavioral therapy.…”
Section: Potential Problemsmentioning
confidence: 99%
“…The IBS and CWP studies were RCT studies, whereas the DMT2 was a pilot. The RCTs showed positive results concerning catastrophizing, acceptance and illness impact at a 3 and 5-month follow-up, respectively [20,21]. The participants' subjective experiences of the interventions in all studies were mostly positive.…”
Section: Background Of the Studymentioning
confidence: 89%
“…The intervention concept, use of mobile technology to deliver the treatment based on behavioral therapy in a written format, was developed and tested first in the Netherlands in persons with irritable bowel syndrome (IBS) [20]. Later the intervention concept was refined and tested in Norway in persons with chronic widespread pain (CWP) and DMT2, respectively [21,22].…”
Section: Background Of the Studymentioning
confidence: 99%